2013
DOI: 10.1111/jace.12272
|View full text |Cite
|
Sign up to set email alerts
|

“Metakaolin‐Slag‐Clinker Blends.” The Role of Na+ or K+ as Alkaline Activators of Theses Ternary Blends

Abstract: This article reports on research into the use of solid alkalis (Na 2 CO 3 and K 2 CO 3 ) as activators to obtain hybrid cement (cement whose hydration generates a mix of C-A-S-H and (N,C)-A-S-H gels) from a blend of 20% cl ınker + 40% blast furnace slag + 40% metakaolin. More specifically, the study aimed to determine the effect of activator dosage (5 and 8 wt%) and type of alkaline cation (Na + or K + ) on the 2-and 28-d mechanical strength of the end materials. The findings showed that the highest mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 46 publications
(80 reference statements)
5
23
0
Order By: Relevance
“…Recent NMR spectroscopy studies on alkali‐activated slags by the authors indicated an increase in mean silicate chain length (a measure of the degree of polymerization of the gel) with increase in M s in the ranges mentioned in this study . These effects have been reported to be responsible for better mechanical properties . Beyond a certain M s (typically 2.5), excess silicates interfere with gel polymerization, and the strengths have been shown to reduce.…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…Recent NMR spectroscopy studies on alkali‐activated slags by the authors indicated an increase in mean silicate chain length (a measure of the degree of polymerization of the gel) with increase in M s in the ranges mentioned in this study . These effects have been reported to be responsible for better mechanical properties . Beyond a certain M s (typically 2.5), excess silicates interfere with gel polymerization, and the strengths have been shown to reduce.…”
Section: Resultssupporting
confidence: 47%
“…Based on previous studies, the optimum n value was found to be 0.05. A lower n value results in a lower alkalinity and consequently reduced dissolution and reaction rates whereas a higher value contributes to leaching of excess alkalis and carbonation . The sodium silicate solution used here has a solids content of 36% and a molar M s of 3.3, while the potassium silicate solution has a solids content of 44% and a molar M s of 3.29.…”
Section: Experimental Programmentioning
confidence: 99%
“…The alkali activators can be divided into two categories, namely alkalis such as NaOH, KOH, Na 2 CO 3 and K 2 CO 3 and silicate additives such as Na 2 SiO 3 and K 2 SiO 3 Fernández-Jiménez et al 2013;Xiong et al 2004). Table 3 summarizes some experiences for controlling alkali activators from various research groups.…”
Section: Raw Aluminosilicate Materials and Alkali Activatorsmentioning
confidence: 99%
“…However, conflicting results were reported when comparing the effects of Na þ and K þ . Fernández-Jiménez et al (2013, 2006a reported that Na þ has a greater capacity than K þ to accelerate the setting and hardening reactions in fly ash geopolymerization when all the other conditions are kept the same, and thus the sodium geopolymers had higher mechanical strength than potassium geopolymers. Based on the results of strength measurements and SEM and MAS NMR analyses, they attributed the observed differences to a balance of two opposing mechanisms: (1) the higher alkalinity of the potassium salts, which induces higher aluminosilicate solubility than sodium salts and (2) the smaller ionic radii of Na þ , which gives the sodium ion a higher charge density than K þ .…”
mentioning
confidence: 99%
See 1 more Smart Citation